Buy Now Pay Later Adoption and Financial Literacy: Determinants, Debt Risks, and Implications for Financial Well-Being Among Young Adults in Tanzania - Charles, Abraham (Southeast Asian Business Review, 2026)
The rapid growth of Buy Now, Pay Later (BNPL) services in developing economies such as Tanzania engenders a multifaceted dilemma: although it enhances access to credit and stimulates expenditure, it may concurrently deepen financial instability, particularly among the young adults. This work examined how BNPL adoption influences both consumer behavior and long-term financial well-being, and whether financial literacy can moderate the relationship be-tween BNPL adoption and financial stability. Using a quantitative approach and structural equation modeling, the research found that BNPL usage strongly predicts higher spending levels. Unexpectedly, the results indicated a minimum shield of financial literacy to users from financial instability. Factors like age and income shaped adoption patterns, and most importantly, BNPL usage was linked to reduced savings and higher debt, undermining long-term financial health. These results suggest that although BNPL fuels short-term consumption, it threatens financial resilience and since financial knowledge alone isn’t enough to protect users, the study under-scores the urgent need for regulatory safeguards and targeted consumer protections in digital credit markets.